Indonesia Stock Exchange Resilience toward Crisis; Study Case of US and China Trade War - Helma Malini; Edwin Suwantono (LPPM of NAROTAMA UNIVERSITY, 2021)
This paper investigates the resilience’s of Indonesia stock Exchange toward the US and China trade war. Emphasis is put on the influence of US and China trade war since 2016. We analyze data using five major sectoral indexes in IDX (Consumer Goods Industry Sector, Agriculture Sector, Infrastructure, Utility and Transportation Sector, Miscellaneous Industry Sector, and Mining Sector) using volatility modelling of Autoregressive Distributed Lag (ARDL) & Generalized Method of Moments (GMM) methods to find the correlation and co- integration between selected sector US and China trade war. We find inconclusiveness and no co-integration on correlated markets although the trade wars have impact for each sectoral index by using ARDL. GMM method showed a significance short-run relationship and long-run relationship. The market disequilibrium takes nearly about one and half week to clear any disequilibrium toward certain shocks or impacts.